Predictive value of neutrophil to lymphocyte ratio for the clinical outcomes of acquired immune deficiency syndrome: a systematic review and meta-analysis - Fuyu Guo; Jiamei Chen; Hengkai Zhang (Frontiers in Medicine)
ObjectiveThis study aimed to explore the predictive value of the neutrophil-to-lymphocyte ratio (NLR) for outcomes in Acquired Immune Deficiency Syndrome (AIDS) patients.MethodsPubMed, Embase, Cochrane, and Web of Science were conducted to search literature up to May 2024 and cohort and case–control studies were included. The primary outcomes were mortality and progression-free survival (PFS). Pooled odds ratios (ORs) or hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated using a random-effects model. We conducted sensitivity analyses to assess result stability, reliability, and subgroup analyses to identify sources of heterogeneity using Review Manager 5.4.1. Egger’s tests were performed with Stata 15.1, and funnel plots were generated using Review Manager 5.4.1. Microsoft Excel was used for the initial data summarization.ResultsFourteen studies involving 30,752 AIDS patients were included. The pooled data showed higher NLR significantly associated with increased mortality (OR: 1.85, 95% CI: 1.43–2.41, p < 0.00001) and shorter progression-free survival (PFS) (HR: 2.46, 95% CI: 1.32–4.59, p = 0.005). Subgroup analyses revealed that NLR’s predictive value was greater in studies with post-ART measurements. Sensitivity analyses show stable and reliable results. Egger’s test and funnel plot analysis revealed no significant publication bias.ConclusionNLR is a key prognostic biomarker for predicting mortality and progression-free survival (PFS) in AIDS patients. Incorporating NLR into predictive models may improve prognostic assessments and guide clinical decision-making.Systematic Review RegistrationPROSPERO (CRD42024532918: https://www.crd.york.ac.uk/PROSPERO).